Development of Particulate Matter Monitors based on Light Scattering Method - Liu, Junjie; Yu, Laihua; Ye, Jing; Huang, Zhihuang; Lu, Jiazhen; Liu, Yue (Manufacturing Technology Journal, 2023)
PM2.5 and PM10 measurement technique based on light scattering usually exhibit inaccurate measurement results in their applications. For improving the reliability of this method for PM2.5 and PM10 measurement, systematic research on the structure optimization of single particle light scattering sensors (SPLSS), calibration of SPLSS, and PM2.5/PM10 monitor development are carried out. Frist, by simulating and optimizing light scattering parameters, light scattering signals varied monotonically with particle size could be obtained, and thereby capability of accurate size-identifying can be established. Then, by developing threshold comparison circuit and calibration device, particle size channel of SPLSS or monitor could be divided, and particle counting efficiency could be corrected. Finally, by obtaining empirical values of parameters, i.e., heating temperature, particle density, involved in the developed dynamic heating system and PN-PM algorithm, interference of humidity and particle characteristics can be effectively eliminated, thus particle mass concentration (PM) could be calculated according to particle number concentration (PN) in each channel. The results show that the developed monitor has good accuracy by comparing it in atmospheric air with reference methods of PM2.5/PM10.
Keywords: PM2.5; PM10; Mass concentration; Sensor; Calibration